The Influence of Visual Aids, Cooperative Learning, and Classroom Environment on English Vocabulary Acquisition of the fourth-grade students at Elementary Islamic School - Fitriani; Indawan Syhari; Mulyadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aimed to examine the influence of visual aids, cooperative learning, and classroom environment on the English vocabulary acquisition of fourth-grade students at Elementary Islamic School. A quantitative method with a correlational design was used, involving 139 students as the population. Data were collected through questionnaires and a vocabulary test, then analyzed using multiple linear regression in SPSS. The results showed that none of the three independent variables significantly influenced vocabulary acquisition. Pearson correlation values indicated weak and non-significant relationships for visual aids (r = -0.038), cooperative learning (r = -0.011), and classroom environment (r = 0.007). The regression model yielded an R² value of 0.002, meaning that the combined variables explained only 0.2% of the variance in vocabulary scores. The findings suggest that although these factors are widely supported by theory, their implementation in this context may not have been effective. Issues such as low instrument reliability, the use of a Yes/No scale, and unmeasured external factors may have contributed to the results. Further research is needed to explore additional variables that may better support vocabulary development in young learners.